The mediating role of the future time perspective in the relationship between global climate change awareness and hope for the prevention of climate change. (December 2022) - Çıplak, Ersun
This study examined the mediating role of the future time perspective in the relationship between climate change awareness and the hope of preventing the climate emergency. The study group consisted of 398 adults. The data were collected using the awareness scale of university students about global climate change, climate change hope scale, and the Zimbardo time perspective inventory future time perspective subscale. The data were analyzed by SPSS 25.0, LISREL 8.70, and PROCESS v3.4 for SPSS. The results showed that the mediating role of the future time perspective in the relationship between climate change awareness and the hope of preventing climate change was statistically significant. The results also demonstrated that the future time perspective should be taken into account in interventions to increase the awareness and hope of individuals about climate change. This may be particularly important in countries such as Turkey, where action plans to prevent climate change have only recently come into force.